Religiosidade popular, espaço-tempo reconciliador, aspectos subjetivos da religião : um olhar para a romaria de Frei Damião em São Joaquim do Monte - PE - Vieira, Heleno José (2013)
After years of participating in and observing the call frei Damião, Pilgrimage in São Joaquim do Monte, Pernambuco, feeling and analyzing the manifestations of faith lived by pilgrims, our epistemological interest turned to the culture of pilgrimage and its Web of meanings, trying to learn what the experience of pilgrimage means for the local community and to the pilgrims. We substantiate our research on the contributions of Geertz and García Cancline, by agree both with the idea that culture, in our case that is popular, "a context", within which the forms of religiosity "can be applet descript [a] s in an intelligible manner i.e. applet descript [a] with density", as with the idea that popular culture is a "hybrid" and cultureas such, should be analysed. Throughout our research we found that the phenomena of pilgrimages is not an exclusive and unique reality of Christianity. Is probably the first mass phenomenon of history and still present in other religious experiences, so strong and striking, as is the case of Islam and Hinduism. In all cases, we can say that it is fetched by be source of reconciliation. In conclusion, we agree with Terrin, that "the two dimensions the real and the imaginary coexist so exceptional in pilgrimage as perhaps no other phenomenon".